The Determination of Alpha-fetoprotein, Golgi protein-73 and Glypican-3 Levels in Chronic Viral Hepatitis B Patients with Fibrosis in Baghdad Gastroenterology and Hepatology Hospital - Mahmoud, Suhad Mohammed; Hassan, Athraa Zaidan; Hassan, Salah Mahdi; Alwaysi, Safaa Abdulkareem (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2025)
Background: Chronic hepatitis B (CHB) infects the liver and is considered the leading cause of fibrosis and hepatocellular carcinoma (HCC). As liver biopsy is invasive, biomarkers that predict CHB noninvasively could affect the overall complication of this dreaded disease. Objective: The aim of this study was to evaluate the use of alpha-fetoprotein (AFP), Golgi protein-73 (GP73), and glypican-3 levels as new predictive biomarkers for assessing hepatitis B infection patients with fibrosis. Method: This study included 60 participants and classified 30 chronic hepatitis B patients with fibrosis and 30 apparently healthy subjects who served as controls. The liver function test was performed for all participants, in addition to serum levels of AFP, GP73, and GPC3 level by using the sandwich ELISA technique. Liver fibrosis was assessed using FibroScan. Results: The current study showed that GP73 and GPC3 levels were significantly elevated in the chronic hepatitis B with fibrosis group; furthermore, AFP levels were significantly different in the chronic hepatitis B with fibrosis group compared to the control group. Conclusions: The current study demonstrated that GP73 alone or in combination with GPC3 level can be considered as an effective biomarker for assessing fibrosis among patients with CHB.